#### Answer

$S(p)=\frac{1}{2\sqrt p}-1$

#### Work Step by Step

$S(p)=\sqrt p-p$
Use the power rule.
$S(p)=\frac{1}{2\sqrt p}-1$

Published by
Cengage

ISBN 10:
1285740629

ISBN 13:
978-1-28574-062-1

$S(p)=\frac{1}{2\sqrt p}-1$

$S(p)=\sqrt p-p$
Use the power rule.
$S(p)=\frac{1}{2\sqrt p}-1$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.